A Case of Disseminated Mycobacterium avium Infection in a Dog in Greece - V. Kontos; E. I. Papadogiannakis; G. Mantziaras; M. Styliara; S. Kanavaki (Case Reports in Veterinary Medicine)
A Basset Hound dog was presented with anorexia, fever, diarrhea, significant level of splenomegaly, and enlargement of mesenteric and superficial lymph nodes. Cytology of fine-needle-aspiration material, obtained from popliteal lymph node, revealed macrophages with intracytoplasmic, nonstaining, slender, rod-like structures, indicative of mycobacteria. Bacterial culture of lymph node aspirated material produced a colony which by means of molecular techniques (PCR amplification and hybridization of PCR products) was subsequently identified as Mycobacterium avium. This is the first report of disseminated M. avium infection in a dog in Greece.